Atividade farmacológica de mel orgânico da Mata Atlântica brasileira nos componentes microbiano e inflamatório da doença periodontal : Pharmacological activity of brazilian honey from the brazilian Atlantic Forest in the microbial and inflammatory components of periodontal disease - Romário-Silva, Diego, 1993- (2021)
Orientador: Pedro Luiz Rosalen